Etika Lingkungan Hidup dalam Program Pemberdayaan Masyarakat Berbasis Pertanian Ramah Lingkungan - Ramadhani Ramadhani; Articha Zahra; Suci Wulandari; Sintia Andini; Nabil Hani Putra; Desi Nurhabibah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Environmental damage caused by unsustainable conventional agricultural practices has become a serious problem, impacting soil quality, water quality, and biodiversity. This situation demands a new approach that focuses not only on increasing production but also on environmental sustainability. This study aims to analyze the role of environmental ethics in community empowerment programs based on environmentally friendly agriculture, examine their implementation, and identify their impact on the sustainability of agricultural systems. The method used was a literature review, examining various scientific sources, including journals, books, and relevant research reports from the past ten years. Data analysis was conducted using descriptive qualitative techniques through the process of identifying, categorizing, and synthesizing previous research findings. The results indicate that environmental ethics plays a fundamental role as a normative foundation in shaping community ecological awareness. The integration of environmental ethical values into empowerment programs can encourage changes in community behavior from exploitative patterns to more environmentally friendly and sustainable agricultural practices. The implementation of a participatory approach in community empowerment has been shown to increase community capacity, independence, and active participation in natural resource management. In addition to its positive impact on ecological aspects, the implementation of environmentally friendly agriculture also contributes to improved economic welfare and strengthened community social cohesion. However, various obstacles such as limited knowledge, access to technology, and resistance to change remain challenges to its implementation. Therefore, synergy between the government, educational institutions, and the community is needed to support the sustainability of environmental ethics-based empowerment programs.